The impact of a dairy milk recovery beverage on bacterially stimulated neutrophil function and gastrointestinal tolerance in response to hypohydration inducing exercise stress - Costa, R. J.; Camões-Costa, V.; Snipe, R. M.; Dixon, D.; Russo, I.; Huschtscha, Z. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The study aimed to determine the impact of a dairy milk recovery beverage immediately after endurance exercise on leukocyte trafficking, neutrophil function, and gastrointestinal tolerance markers during recovery. Male runners (N = 11) completed two feeding trials in randomized order, after 2 hr of running at 70% VO2max, fluid restricted, in temperate conditions (25 °C, 43% relative humidity). Immediately postexercise, the participants received a chocolate-flavored dairy milk beverage equating to 1.2 g/kg body mass carbohydrate and 0.4 g/kg body mass protein in one trial, and water volume equivalent in another trial. Venous blood and breath samples were collected preexercise, postexercise, and during recovery to determine the leukocyte counts, plasma intestinal fatty acid binding protein, and cortisol concentrations, as well as breath H2. In addition, 1,000 µl of whole blood was incubated with 1 µg/ml Escherichia coli lipopolysaccharide for 1 hr at 37 °C to determine the stimulated plasma elastase concentration. Gastrointestinal symptoms and feeding tolerance markers were measured preexercise, every 15 min during exercise, and hourly postexercise for 3 hr. The postexercise leukocyte (mean [95% confidence interval]: 12.7 [11.6, 14.0] × 109/L [main effect of time, MEOT]; p < .001) and neutrophil (10.2 [9.1, 11.5] × 109/L; p < .001) counts, as well as the plasma intestinal fatty acid binding protein (470 pg/ml; +120%; p = .012) and cortisol (236 nMol/L; +71%; p = .006) concentrations, were similar throughout recovery for both trials. No significant difference in breath H2 and gastrointestinal symptoms was observed between trials. The total (Trial × Time, p = .025) and per cell (Trial × Time, p = .001) bacterially stimulated neutrophil elastase release was greater for the chocolate-flavored dairy milk recovery beverage (+360% and +28%, respectively) in recovery, compared with the water trial (+85% and -38%, respectively). Chocolate-flavored dairy milk recovery beverage consumption immediately after exercise prevents the decrease in neutrophil function during the recovery period, and it does not account for substantial malabsorption or gastrointestinal symptoms over a water volume equivalent.